(untitled) (Journal of Telenursing (JOTING), 2023)
This study examines the impact of sleeping late at night and its relationship with the incidence of malaria. This research method uses observational analytics with a cross-sectional study approach. The study results showed that the habit of sleeping late at night on malaria incidence obtained a P value of 0.000. In conclusion, there is a relationship between the practice of sleeping late at night and the incidence of malaria at the Samabusa Community Health Center, Nabire Regency. Keywords: Late Night Sleeping Habits, Malaria, Samabusa